Digital Transformation in Accounting: A Systematic Review of New Trends - Emilla Dwi Nurrahma; Naila Fadilah; Gunawan Aji (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2025)
This study aims to identify trends, key issues, and technological developments in digital accounting through a Systematic Literature Review (SLR) approach. Articles were sourced from Google Scholar, published between 2020 and 2025, and focused on Indonesian-language literature. Out of 224 initial articles, 25 met the inclusion criteria and were analyzed using qualitative and bibliometric methods. The findings show that the most dominant topics include the application of technologies such as AI, blockchain, big data, and cloud computing, which enhance efficiency and transparency in financial reporting. However, significant challenges remain, including limited infrastructure, human resource competencies, and the need for adaptive regulations. The study also highlights the urgency of reforming accounting education curricula and strengthening digital ethics. This research offers both theoretical and practical contributions by mapping the direction of digital accounting development in Indonesia and identifying research gaps that could inform future studies and policy-making. Thus, accounting digitalization is not merely a technological trend, but a strategic necessity in navigating the digital economy era.